2018
DOI: 10.1111/rda.13274
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes in vitro activation of ovine primordial follicles by reducing DNA damage and enhancing granulosa cell proliferation via phosphatidylinositol 3‐kinase pathway

Abstract: We aimed to study the effects of resveratrol on the morphology, DNA fragmentation, follicular activation and cell proliferation after in vitro culture of ovine ovarian tissue, and to verify if PI3K pathway is involved in resveratrol action in the sheep ovary. Ovaries were collected and divided into fragments. One fragment was fixed for histology (fresh control). The remaining fragments were cultured for 7 days in control medium (α-MEM ) alone or with resveratrol (2, 10 or 30 µM). After culture, ovarian tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…In cancer cells, RES has a powerful anti-inflammatory effect and antioxidative role and has been found to induce cellular apoptosis and cell-cycle arrest [40,41,42]. Bezerra et al [43] discovered that RES promotes primordial follicle activation by reducing DNA fragmentation and stimulates granulosa cell proliferation through activation of the PI3K pathway. Li et al [44] showed that RES reduces oxidative stress and inhibits apoptosis in granulosa cells by activating the PI3K/AKT signaling pathway in a rat model of POI.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, RES has a powerful anti-inflammatory effect and antioxidative role and has been found to induce cellular apoptosis and cell-cycle arrest [40,41,42]. Bezerra et al [43] discovered that RES promotes primordial follicle activation by reducing DNA fragmentation and stimulates granulosa cell proliferation through activation of the PI3K pathway. Li et al [44] showed that RES reduces oxidative stress and inhibits apoptosis in granulosa cells by activating the PI3K/AKT signaling pathway in a rat model of POI.…”
Section: Discussionmentioning
confidence: 99%
“…However, marker expression varied between the investigated species, as well as with the maturation stage of isolated granulosa cells. For example, Oct-4 expression was detected in human but not in porcine model immediately after isolation of GCs [ 44 , 45 ]. While this fact is one of the many indicators that the stemness of granulosa cells needs to be further investigated to become a consensus, it is certainly a population of high potential for possible applications in the fields of modern medicine.…”
Section: Stemness Of Human Ovarian Granulosa Cellsmentioning
confidence: 99%
“…These findings stay in accordance with results of Bazerra et al, reporting that resveratrol enhances primordial follicle activation and decreases the level of DNA fragmentation in in vitro cultures of ovine ovarian tissue. Furthermore, they have also shown the ability of resveratrol to stimulate GCs proliferation via activation of the PI3K pathway [ 44 , 97 ]. PI3K is known as one of the fundamental signaling pathways, involved in follicle activation in rodents [ 44 ].…”
Section: The Modulation Of Granulosa Cell Physiological Processes mentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ROS can retard oocyte maturation and lead to cell death [30, 31]. Supplementation of the environment with antioxidants could decrease oxidative damage and thus protect cells [3234]. N-Acetyl-L-cysteine (NAC) is less toxic and can increase intracellular glutathione (GSH) levels [35, 36], and GSH plays a key role in preventing oxidative stress in oocytes [37].…”
Section: Introductionmentioning
confidence: 99%